2008
DOI: 10.1111/j.1365-2516.2008.01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of von Willebrand factor in haemostasis and thrombosis

Abstract: Summary. The physiological protection against bleeding is secured by platelet adhesion to the site of injury and sealing of the defect. The first step involves the arrest of platelets that have adhered to subendothelial structures, primarily collagen, at the site of injury. Under conditions of low shear rates, platelet adhesion to the damaged vessel wall is mediated by several proteins, including von Willebrand factor (VWF). However, under conditions of high shear, aggregation occurs only in the presence of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
155
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 125 publications
(156 reference statements)
3
155
0
5
Order By: Relevance
“…62 The influence of shear stress on the activity of platelets and vWF has been discussed in other review articles. 57,58,63,115 Others have linked the deterioration in cerebral microcirculation (cerebral hypoperfusion) to the onset of protein conformational disorders such as Alzheimer's disease. [116][117][118] It is suggested that reduced cerebral blood flow may replace old age as a risk factor for Alzheimer's disease.…”
Section: Implications In Physiology and Bioprocessingmentioning
confidence: 99%
“…62 The influence of shear stress on the activity of platelets and vWF has been discussed in other review articles. 57,58,63,115 Others have linked the deterioration in cerebral microcirculation (cerebral hypoperfusion) to the onset of protein conformational disorders such as Alzheimer's disease. [116][117][118] It is suggested that reduced cerebral blood flow may replace old age as a risk factor for Alzheimer's disease.…”
Section: Implications In Physiology and Bioprocessingmentioning
confidence: 99%
“…D-dimer is the FDP whose level is used as a clinical indicator of ongoing coagulation. D-dimer increases in thrombotic conditions such as disseminated intravascular coagulation, deep venous thrombosis, and pulmonary embolism (5,10,23). We analyzed the levels of vWF and D-dimer in mouse blood and the number of microthrombi in the liver.…”
Section: Role Of the Osmotically Regulated Transcription Factor Nfat5mentioning
confidence: 99%
“…For example, arterial thrombosis can be triggered by rupture of atherosclerotic plaques that leads to endothelial damage. However, venous thrombosis can also occur in the presence of an intact endothelium, making the triggering mechanism less apparent (1,4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first -mediates the adhesion of platelets to the subendothelial matrix after vascular injury (16,17) and the second -protects the VIII factor from proteolytic degradation (18). vWF is released into circulation by secretion from endothelial cells (accumulates in Weibel-Palade bodies) and platelets (their alpha granules) (19,20).…”
Section: Introductionmentioning
confidence: 99%